A review of carbon dioxide as a refrigerant in refrigeration technology - Maina, Paul; Huan, Zhongjie (South African Journal of Science, 2015)
Tough environmental laws and stringent government policies have revolutionised the refrigeration sector, especially concerning the cycle fluid known as the refrigerant. It has been observed that only natural refrigerants are environmentally benign. When other refrigerant qualities are considered, especially those relating to toxicity and flammability, carbon dioxide emerges as the best among the natural refrigerants. However, carbon dioxide based refrigerants are not without drawbacks. Even though the use of R744 – a carbon dioxide based refrigerant gas – has solved the direct effect of emissions on the environment, studies to investigate the indirect effects of these systems are needed. Improvement in existing technical solutions and the formulation of additional solutions to existing R744 refrigeration problems is paramount if this technology is to be accepted by all, especially in areas with warm climates. National policies geared to green technologies are important to clear the way and provide support for these technologies. It is clear that carbon dioxide is one of the best refrigerants and as environmental regulations become more intense, it will be the ultimate refrigerant of the future.